THE IMPLICATION OF BRAIN GAIN ON BRAIN DRAIN PHENOMENON IN OVERCOMING THE PROBLEM OF EDUCATED UNEMPLOYMENT IN INDONESIA - Duwi Yunitasari; Khusnul Khotimah; Moehammad Fathorrazi (Universitas Padjadjaran, 2021)
The high number of educated unemployment of university graduates is a significant problem in Indonesia. This study aims to find out the effect of brain drain, economic growth, and provincial minimum wage on educated unemployment of university graduates in Indonesia. In this study, we were implementing brain gain on brain drain in Indonesia. This study uses panel data regression that describes the relationship between independent variable and dependent variables. There are two models from the panel data regression method: the Chow test and Hausman Test. The regression model used is fixed-effect model. The data is secondary data collected from Statistical Central Agency (BPS) and National Agency for Placement and Protection of Indonesia Labour (BNP2TKI) in 2014-2018. The results show that brain drain and economic growth influence the educated unemployment of university graduates but the provincial minimum wage does not have a significant relationship with the educated unemployment of University graduates in Indonesia.